PENGARUH PEMERAMAN TERHADAP TANAH LEMPUNG YANG DICAMPUR DENGAN ASPAL EMULSI - Widyatmika, I Nyoman Hasta; Aribudiman, I Nyoman; Putra, Tjok Gede Suwarsa (Jurnal Ilmiah Teknik Sipil, 2016)
Clay soil is not suitable to use as a building foundation. This is because clay soil is easily to get expand and shrink. As the water in the soil increased, the clay soil will expand. On the other hand, as the water content on the soil decreased, clay soil will be experiencing a very high shrinkage level. This expand and shrink behaviors of this soil will cause damage to the construction above it so that the soil needs to be improved. One of the soil improvement is to do stabilization. Stabilisation is away to improve the soil’s nature behavior by adding or mixing additional specified material which is called additive. A stabilization is to mix the clay soil with emulsion asphalt and is followed with aging process. This research is to investigate the characteristic of the soil and the effect of adding the emulsion asphalt and the aging process to the clay soil stabilitation. The clay soil is added to the emulsion asphalt using mixing percentage of 0%, 3%, 6%, 9% and the aging were held in: 2 days, 4 days, 6 days. The data analysis consisted of filter analize, water content, specific gravity, atterberg limits, soil compaction, free compressive strength and CBR. The study resulted the average IP value of 20,675% showing the clay soil in North Padangsambian area in 1 m depth classified to high plasticity. The IP value decreased, with the lowest IP 20,320%, at 9% emulsion asphalt additive. The additional emulsion asphalt and aging process give a significant effect to the expand and shrink behavior which increases the strength of the soil. The highest free compressive strength reached by adding 9% emulsion asphalt, which caused the qu value from 0,417% to 1,025%, ? increase from 11° to 17°, and c value also increase from 0,209 kg/cm² to 0,513 kg/cm². The CBR value is also increasing. For CBR 0,1 inch increased from 7,484% to 9,137% and CBR 0,2 inch increased from 5,081% to 6,520%. The incubation causing the water content on the soil spreads and make the soil become harder and this will cause the qu and c of soil increased.
Keywords: clay soil, emulsion asphalt and aging.